2012
DOI: 10.1111/j.1600-0625.2011.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of RAGE, MAPK and NF‐κB pathways in AGEs‐induced MMP‐9 activation in HaCaT keratinocytes

Abstract: Advanced glycation end products (AGEs) exert divergent effects on the pathogenesis of diabetes complications. Excessive expression of matrix metalloproteinases-9 (MMP-9) is deleterious to the cutaneous wound-healing process in the context of diabetes. However, the effect of AGEs on MMP-9 induction in skin cells and the exact molecular mechanisms involved are still poorly understood. In this study, we investigated the effect of AGEs on the production of MMP-9 in HaCaT keratinocytes and characterized the signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 45 publications
(45 reference statements)
4
71
0
Order By: Relevance
“…It has been reported that AGE-RAGE complex increased TNF-α and MMPs and retarded the wound healing process in diabetic mice. In contrast, the inhibition of AGE-RAGE formation by blocking RAGE resulted in faster wound repair and regeneration [40]. Similarly, the presence of AGE-RAGE complex on fibroblasts reduced the formation of collagen as a necessary compound for wound repairing [41].…”
Section: Diabetic Wound Healingmentioning
confidence: 99%
“…It has been reported that AGE-RAGE complex increased TNF-α and MMPs and retarded the wound healing process in diabetic mice. In contrast, the inhibition of AGE-RAGE formation by blocking RAGE resulted in faster wound repair and regeneration [40]. Similarly, the presence of AGE-RAGE complex on fibroblasts reduced the formation of collagen as a necessary compound for wound repairing [41].…”
Section: Diabetic Wound Healingmentioning
confidence: 99%
“…S100a8/ a9-RAGE predominantly influences mitogen-activated protein kinase activation and NF-κB signaling. 36,37 We detected significant expression changes in multiple cytokines and chemokines, including CXCL1/2, CCL2, CCL3, CCL5, IL-1β, IL-6, IL-12, and TNF-α. These data are supported by previous studies showing that mitogen-activated protein kinase and NF-κB signaling pathways modulate the release of chemokines and cytokines.…”
Section: Downloaded Frommentioning
confidence: 99%
“…RAGE is a transmembrane receptor and mediates activation of intracellular signal transduction pathways after binding diverse ligands such as AGEs, high mobility group box 1 protein (HMGB1), and S100/calgranulins (12,13). Activation of RAGE triggers intracellular signaling that promotes the proinflammatory tran-scriptional factor NF-B (13,14) and the mitogen-activated protein kinase (MAPK) pathway (15,16). Given the recent studies reporting that AGEs and RAGE are involved in diabetic nephropathy, several methods have been developed to cure chronic kidney disease by interfering with the pathophysiological effect of AGE (12).…”
Section: Autosomal Dominant Polycystic Kidney Disease (Adpkd)mentioning
confidence: 99%